Resveratrol: Chemoprevention with red wine - Palavan-Ünsal, Narçin; ARISAN, ELİF DAMLA (İstanbul Kültür Üniversitesi, 2007)
According to epidemiological studies, western diet has disadvantages because of cancer prevalence more than Mediterranean or Asia people who consume more vegetables and fruits. Resveratrol (trans-3,4,5-trihydroxystilbene) which is highly found in grapes, berries has received attention for its potential chemopreventive and antitumor effects in experimental systems. Because of high resveratrol content, researchers noted that red wine has multidimensional benefits for cardiovascular health. Resveratrol also protects neuron cells from other well known chemotherapeutics. The molecular function of resveratrol in chemoprevention and carcinogenesis are reviewed by experimental cancer cell models. Resveratrol is going to be a promising molecule in future cancer prevention and therapy models.
Keywords: Resveratrol; chemoprevention; carcinogenesis; apoptosis; apoptoz; karsinogenezis; kemoprevensiyon